2010
DOI: 10.3346/jkms.2010.25.10.1431
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Papilloma Virus Infections and Cervical Cytological Abnormalities among Korean Women with Systemic Lupus Erythematosus

Abstract: We performed a multicenter cross-sectional study of 134 sexually active systemic lupus erythematosus (SLE) patients to investigate the prevalence of and risk factors for high risk human papilloma virus (HPV) infection and cervical cytological abnormalities among Korean women with SLE. In this multicenter cross-sectional study, HPV testing and routine cervical cytologic examination was performed. HPV was typed using a hybrid method or the polymerase chain reaction. Data on 4,595 healthy women were used for comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 28 publications
2
33
0
1
Order By: Relevance
“…This come in agreement with Lee et al that found high prevalence of HPV infection (24.6%) among Korean patients with SLE in comparison with 7.9% (p > 0.001) in healthy women (22) . In addition, Tam et al found in SLE patient high prevalence of HPV infection and abnormal pap smears (25%) which statistically increased to 48.5% after 3 years follow up with persistent and multiple HPV infections when compared non-SLE patients with cervical dysplasia (23) .…”
Section: Discussion:-supporting
confidence: 82%
“…This come in agreement with Lee et al that found high prevalence of HPV infection (24.6%) among Korean patients with SLE in comparison with 7.9% (p > 0.001) in healthy women (22) . In addition, Tam et al found in SLE patient high prevalence of HPV infection and abnormal pap smears (25%) which statistically increased to 48.5% after 3 years follow up with persistent and multiple HPV infections when compared non-SLE patients with cervical dysplasia (23) .…”
Section: Discussion:-supporting
confidence: 82%
“…It has been shown that human papillomavirus (HPV) infection occurs more often in patients with SLE, also with the high-risk (oncogenic) subtypes of the virus 103105. A lower percentage of these infections (31.8%) is spontaneously cleared by patients with SLE,106 leading to an increased risk of developing cervical cancer.…”
Section: Resultsmentioning
confidence: 99%
“…[49][50][51] The cumulative prevalence rises from 12.5% at study entry (11.1% high-risk subtype) to 25.0% (20.8% high-risk sub type) after 3 years. Only 14.7% of all incident infections are cleared in this time frame.…”
Section: Human Papillomavirusmentioning
confidence: 98%
“…52 general population as well as the presence of anti-nuclear antibodies (ANAs) at a titration >1:320. 49,51,52 Efficacy of vaccination At least some vaccine-preventable infections are more common in patients with an AIRD than in the general population; therefore, efficacy of vaccination in these patients should be addressed. The aim of vaccination is to reduce morbidity and mortality that is directly or indirectly provoked by infection.…”
Section: Human Papillomavirusmentioning
confidence: 99%